MENTOR EDUCATION AND QUALITY OF PHD STUDIES: CURRENT STATUS AND FUTURE CHALLENGES: Mentor education - Milovanovic, doc. dr Petar; Pekmezovic, prof. dr Tatjana (Medical Research, 2022)
Mentorship is a specific relationship, where an experienced senior investigator provides guidance, support, and advice to navigate a junior colleague through the barriers to becoming an independent researcher. While mentoring is clearly a rewarding duty, it is also associated with a number of challenges. Clearly, mentoring involves many responsibilities, which requires a certain set of skills from the mentor. While many of these skills are learned in the direct interaction with mentees, it would be beneficial if more formal and structured training would be offered to mentors, especially at the beginning of their mentoring careers, so as to avoid frequent mistakes in the mentor–mentee relationship. Hence, the idea is to shift from experience-based mentorship towards professionalization, believing that such an approach would reduce the risk of poor mentoring. At present, many universities offer formal education of mentors. The practice of organized education of supervisors at University of Belgrade Faculty of Medicine started in 2019 with the aim to prepare future mentors to establish productive and responsive relationships with mentees. After a break due to the COVID-19 pandemic, a revised mentoring course was organized in 2022. Survey of the attendees of the two organized courses supported the need for better education of university teachers in terms of mentoring skills and leading of PhD candidates. Indeed, considering that PhD outcomes are largely dependent on the mentor and the successful mentor–mentee relationship, supporting mentoring through formal training and education may be an important step in improving PhD experience and outcomes for both the mentors and the PhD candidates.